Integrating floral trait and flowering time distribution patterns help reveal a more dynamic nature of co‐flowering community assembly processes. (26th August 2020) - Albor, Cristopher; Arceo‐Gómez, Gerardo; Parra‐Tabla, Víctor
Abstract: Species' floral traits and flowering times are known to be the major drivers of pollinator‐mediated plant–plant interactions in diverse co‐flowering communities. However, their simultaneous role in mediating plant community assembly and plant–pollinator interactions is still poorly understood. Since not all species flower at the same time, inference of facilitative and competitive interactions based on floral trait distribution patterns should account for fine phenological structure (intensity of flowering overlap) within co‐flowering communities. Such an approach may also help reveal the simultaneous action of competitive and facilitative interactions in structuring co‐flowering communities. Here we used modularity within a co‐flowering network context, as a novel approach to detect convergent and/or over‐dispersed patterns in floral trait distribution and pollinator sharing. Specifically, we evaluate differences in floral trait and pollinator distribution patterns within (high temporal flowering overlap) and among co‐flowering modules (low temporal flowering overlap). We further evaluate the consistency of observed floral trait and pollinator sharing distribution patterns across space (three geographical regions) and time (dry and rainy seasons). We found that floral trait similarity was significantly higher in plant species within co‐flowering modules than in species among them. This suggests pollinator facilitation may lead to floral trait convergence, but only within co‐flowering modules. However, our results also revealed seasonal and spatial shifts in the underlying interactions (facilitation or competition) driving co‐flowering assembly, suggesting that the prevalent dominant interactions are not static. Synthesis . Overall, we provide strong evidence showing that the use of flowering time and floral trait distribution alone may be insufficient to fully uncover the role of pollinator‐mediated interactions in community assembly. Integrating this information along with patterns of pollinator sharing will greatly help reveal the simultaneous action of facilitative and competitive pollinator‐mediated interactions in co‐flowering communities. The spatial and temporal variation in flowering and trait distribution patterns observed further emphasize the importance of adopting a more dynamic view of community assembly processes. Abstract : Integrating flowering time and floral trait distribution along with patterns of pollinator sharing will greatly help reveal the simultaneous action of facilitative and competitive pollinator‐mediated interactions in co‐flowering communities. The spatial and temporal variation in flowering and trait distribution patterns observed further emphasize the importance of adopting a more dynamic view of community assembly processes. Resumen: Los rasgos florales y el tiempo de floración de las especies, se consideran como de las principales fuerzas que guían las interacciones planta‐planta mediadas por polinizadores. Sin embargo, su papel simultáneo en la mediación del ensamblaje de las comunidades y de las interacciones planta‐polinizadores son poco comprendidas. Debido a que no todas las especies florecen al mismo tiempo, la inferencia sobre interacciones de facilitación o competencia basadas en los patrones de distribución de los caracteres florales, deben considerar la estructura fenológica detallada (intensidad y sobrelapamiento floral) que existe dentro de las comunidades co‐florales. Esta aproximación podría ayudar a revelar la acción simultánea de interacciones de competencia y facilitación en la estructuración de las comunidades. En este trabajo usamos la modularidad dentro del contexto de redes de co‐floración como una aproximación novedosa para detectar patrones convergentes o de sobre‐dispersión en la distribución de rasgos florales y la compartición de polinizadores. Específicamente evaluamos diferencias en los patrones de distribución de rasgos florales y de polinizadores dentro (alto sobrelapamiento floral) y entre módulos co‐florales (bajo sobrelapamiento floral). Más aún, evaluamos la consistencia espacial (tres regiones geográficas) y temporal (temporada seca y de lluvias) de la distribución observada de los rasgos florales y la compartición de polinizadores. Encontramos que la similitud de rasgos florales fue significativamente más alta en especies de plantas dentro de módulos co‐florales que entre especies de diferentes módulos. Este resultado sugiere que la facilitación por polinizadores puede llevar a una convergencia de rasgos florales dentro de los módulos co‐florales. Sin embargo, nuestros resultados también revelaron cambios espaciales y temporales en las interacciones subyacentes (facilitación o competencia) que guían el ensamblaje de co‐floración, sugiriendo que las interacciones prevalentes no son estáticas. Síntesis . Globalmente, en este trabajo proveemos fuertes evidencias de que el uso del tiempo de floración y la distribución de rasgos florales de manera independiente, pueden no ser suficientes para revelar completamente el papel de las interacciones mediadas por polinizadores en el ensamblaje de las comunidades. La integración de esta información con los patrones de compartición de polinizadores ayuda a revelar la acción simultánea de interacciones de facilitación y competencia mediadas por polinizadores en comunidades co‐florales. La variación espacial y temporal en los patrones de distribución de la floración y de los rasgos florales observados, enfatizan la importancia de adoptar una visión más dinámica de los procesos de ensamblaje de las comunidades.